NATURALISME-TEISTIK ABU BAKAR ALRAZI - Isfaroh Isfaroh (UIN Raden Mas Said Surakarta, 2019)
This study aims to look at the construction of Abu Bakar Alrazi's theological theistic naturalism.This study used the historical approach of biographical reconstruction, to understand and explore one's personality by looking at his socio-cultural and intellectual background. This study found, first, as a scientist Alrazi used theistic reasoning of naturalism because of the socio-religious conditions in its time experienced truth manipulation and limited potential, religious communities were prohibited for rational speculation on religion, because they were considered sacred and established. According to Alrazi, this is the reason why the truth becomes silent and its nature is very closed. Second, Razi is a pure rationalism, makes reason as proof of God's existence, because through reason he can think about the problems of life.This study contributes to the development of new thoughts on scientific and Islamic discourse in Indonesia, particularly in the field of Islamic philosophy.